2020
DOI: 10.1111/tbed.13676
|View full text |Cite
|
Sign up to set email alerts
|

Novel genotype definition and genome characteristics of duck circovirus in central and Eastern China

Abstract: Duck circovirus (DuCV) was first identified in mallard ducks with feathering disorder and poor body condition in Germany in 2003

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The topological differences between the tree based on Rep and the complete genome mentioned above indicate the occurrence of recombination events [41]. Rep is considered to be essential for viral replication and plays a crucial role in cellular immunity [6,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The topological differences between the tree based on Rep and the complete genome mentioned above indicate the occurrence of recombination events [41]. Rep is considered to be essential for viral replication and plays a crucial role in cellular immunity [6,42].…”
Section: Discussionmentioning
confidence: 99%
“…Rep is considered to be essential for viral replication and plays a crucial role in cellular immunity [6,42]. Recombination events are also widely found in other viruses, such as porcine circovirus, canine circovirus, pigeon circovirus, duck circovirus and goose circovirus [41,[43][44][45][46]. The hotspot of recombination events is Rep, but it is still relatively conserved in ssDNA viruses, indicating that recombination may have little influence on the diversification of Rep.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that various studies have shown that recombination is the primary driver for the diversification of circoviruses in general ( Julian et al, 2013 ; Zhang et al, 2013 ; Stenzel et al, 2018 ; Ji et al, 2020 ). In this study, 9 statistically supported recombination events were detected within 39 of the 139 GoCV complete genome sequences (including 102 retrieved from GenBank and 37 obtained herein), suggesting the ubiquitous presence of recombination in the evolutionary history of GoCVs ( Table 2 and Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic diversity could occur under selection pressure, which displays the diversity level in numerical form by entropy, namely a higher number indicate relatively higher genetic complexity ( Lourenço et al, 2018 ). Thus, the entropy was calculated based on amino acid sequence by using BioEdit as previously described ( Ji et al, 2020 ). Additionally, codon-specific analyses of the entire Rep and Cap proteins coding region were also assessed using 3 methods performed in the Datamonkey web server: Fixed Effects Likelihood ( FEL ), Fast Unconstrained Bayesian AppRoximation ( FUBAR ), and Mixed Effects Model of Evolution ( MEME ).…”
Section: Methodsmentioning
confidence: 99%
“…Many other viruses can also cross species barriers, including parvoviruses and circoviruses. Parvoviruses have been found in geese, ducks, and canines, and circoviruses have been found in ducks, swine and canines [ 19 , [33] , [34] , [35] , [36] , [37] ].…”
Section: Discussionmentioning
confidence: 99%